Corrosion behaviour of steel and copper as influenced by local atmospheric conditions - S. Hadzi Jordanov, D. Slavkov, A. Dimitrov, P. Paunovic (Balkan Environmental Association (B.EN.A.), 2004)
Corrosion of steel (0147, JUS) and copper (99,99%) was studied during past 18 years in a network of 8 testing sites situated in locations of R. of Macedonia with typical microclimate. Climate conditions were registered simultaneously, in order to establish their effect on the observed phenomena. Weight loss, as well as increase of electrical resistance and time of wetness were periodically registered. Testing in a climate chamber was also performed in order to elucidate the individual effect of the most significant parameters. It was found that the corrosion rate depends strongly on the: atmospheric pollution, humidity and temperature, as well as on the time of wetness of metallic surface; thickness and compactness of accumulated corrosion products; composition and morphology of primary corrosion products; orientation of the corroding metal surface, etc. A model based on the sequentional nature of the corrosion of metals in atmosphere was developed, based on the measured pattern of time-of-wetness and precise insight in the discrete progress of the corrosion process.